2019
DOI: 10.1515/chem-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-199a-5p functions as a tumor suppressor in prolactinomas

Abstract: Prolactinomas are the most frequently observed pituitary adenomas (PAs), and 5%–18% tumors were resistant to the dopamine agonists (DAs). MicroRNAs (miRNAs) dysfunction play a key role in tumorigenesis. Agilent miRNA and an expression chip were used for six prolactinomas and three normal pituitary specimens. Differentially expressed genes were confirmed by RT-qPCR. The level of DDR1 and SAT1 was determined with tissue micro-array (TMA) and western blot. A MMQ cell line was used for functional experiments. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…To functional prove miR-199a-5p effect, the authors demonstrated that overexpression of miR-199a-5p suppressed cell differentiation and invasive behaviour of pituitary tumour cells. Interestingly, the miR-199a-5p overexpression downregulated SAT1 protein and mRNA levels (Table 1 ) [ 121 ].…”
Section: Noncoding Rna Regulation Of Polyamine Metabolism In Cancermentioning
confidence: 99%
“…To functional prove miR-199a-5p effect, the authors demonstrated that overexpression of miR-199a-5p suppressed cell differentiation and invasive behaviour of pituitary tumour cells. Interestingly, the miR-199a-5p overexpression downregulated SAT1 protein and mRNA levels (Table 1 ) [ 121 ].…”
Section: Noncoding Rna Regulation Of Polyamine Metabolism In Cancermentioning
confidence: 99%